2004
DOI: 10.1097/01.pgp.0000130109.80359.57
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Apoptosis-Related Proteins in Adenomyotic Uteri Treated with Danazol and GnRH Agonists

Abstract: The biologic properties of adenomyosis and the effects of therapeutic agents on adenomyosis were evaluated with immunohistochemistry, terminal deoxy-nucleotidyl transferase-mediated dUTP-biotin nick end-labeling (TUNEL) method, transmission electron microscopy, and analysis of genomic abnormality. In the adenomyotic endometrium, estrogen receptor (ER) expression was more intense than in the eutopic endometrium during the secretory phase, and bcl-2 was constantly expressed throughout the menstrual cycle. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Until now, few reports have described HIFU ablation combined with GnRH-a pre-treatment for diffuse adenomyosis with a volume greater than 300 cm 3 and clinical follow-up after 12 months. Our study showed that after treatment with GnRH-a, the sizes of most uteri and lesions were clearly reduced and that vascular flow decreased, as observed in other studies [2,3]. The MR enhancement images or CEUS images showed that the non-perfused area indicated temporary ischaemic infarction in some lesions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Until now, few reports have described HIFU ablation combined with GnRH-a pre-treatment for diffuse adenomyosis with a volume greater than 300 cm 3 and clinical follow-up after 12 months. Our study showed that after treatment with GnRH-a, the sizes of most uteri and lesions were clearly reduced and that vascular flow decreased, as observed in other studies [2,3]. The MR enhancement images or CEUS images showed that the non-perfused area indicated temporary ischaemic infarction in some lesions.…”
Section: Discussionsupporting
confidence: 88%
“…GnRH-a causes pituitary GnRH receptor desensitisation and leads to temporary amenorrhoea, which is also called reversible drug oophorectomy. GnRH-a may improve symptoms caused by adenomyosis by suppressing cell proliferation, inducing apoptosis and diminishing the volumes of the uterus and lesion [2,3]. Meanwhile, GnRH-a has an inhibitory effect on the ovaries and leads to similar complaints during menopause; moreover, the most worrisome outcome in women afflicted with adenomyosis is re-occurrence after withdrawal of the medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these represent the same factors contributing to atypical hyperplasia and endometrial polyps through the creation of a hyper-estrogenic status. An overexpression of estrogen receptors in AM foci has been suggested as evidence of this possible association (8,29) supported by the fact that the concomitant EEC diagnosed was frequently of type I, typical of a hyper-estrogenic status and endometrial hyperplasia (3,30).…”
Section: Discussionmentioning
confidence: 93%
“…First, danazol, an androgen analog used for treatment of endometriosis, directly binds to the AR of endometriotic tissue [58] and decreases the expression of Bcl-2 (a suppressor for apoptosis) [59], resulting in the cell death of endometriotic tissue. Second, an animal study has shown that danazol in vivo reduces AR, estrogen receptors, and progesterone receptors of the endometrium [60].…”
Section: Discussionmentioning
confidence: 99%